Protection of Women and Children in Crisis: Post-Disaster Social, Economic, and Political Support and Barriers to Palu - Jamaluddin, Indar Ismail; Daswati, Daswati; Nuraisyah, Nuraisyah (Universitas Teuku Umar, 2025)
This study analyzes the support and obstacles in protecting women and children in crisis situations, focusing on the socio-economic and political conditions influencing Central Sulawesi Provincial Regulation No. 3 of 2019 on the Protection of Women and Children from Violence after the 2018 earthquake, tsunami, and liquefaction in Palu City. Using a descriptive qualitative approach, 15 purposively selected informants representing the pentahelix elements were involved. Data were obtained through in-depth interviews, observations, and documentation, and analyzed using the socio-economic and political variables of Van Meter and Van Horn (1975) policy implementation model, following the stages of data condensation, display, and conclusion drawing (Miles et al., 2014). Secondary data analysis employed bibliometric mapping via VOSviewer. Findings reveal that limited economic resources remain the primary barrier to preventing and addressing violence, while entrenched customary norms and unresponsive bureaucracy heighten vulnerability. Positive drivers include community participation, women’s organizations, media engagement, and progressive regulations, though private sector involvement remains limited. Public opinion largely supports the policy, yet political elite attention is inconsistent. The study concludes that effective post-disaster protection requires sustained funding, consistent political commitment, and cross-sectoral coordination, recommending stronger public–private partnerships and greater community engagement to ensure long-term protection for vulnerable groups.